Parenting Styles and Adolescents’ School Adjustment: Investigating the Mediating Role of Achievement Goals within the 2 × 2 Framework - Xiang, Shiyuan; Liu, Yan; Bai, Lu (Frontiers in Psychology, 2017)
This study examines the multiple mediating roles of achievement goals based on a 2 × 2 framework of the relationships between parenting styles and adolescents’ school adjustment. The study sample included 1061 Chinese adolescent students (50.4% girls) between the ages of 12 and 19, who completed questionnaires regarding parenting styles (parental autonomy support and psychological control), achievement goals (mastery approach, mastery avoidance, performance approach, and performance avoidance goals) and school adjustment variables (emotion, students’ life satisfaction, school self-esteem, problem behavior, academic achievement, and self-determination in school). A structural equation modeling (SEM) approach was used to test our hypotheses. The results indicated that parental autonomy support was associated with adolescents’ school adjustment in an adaptive manner, both directly and through its positive relationship with both mastery and performance approach goals; however, parental psychological control was associated with adolescents’ school adjustment in a maladaptive manner, both directly and through its positive relationship with both mastery and performance avoidance goals. In addition, the results indicated that mastery avoidance goals suppressed the relationship between parental autonomy support and adolescents’ school adjustment, and performance approach goals suppressed the relationship between this adjustment and parental psychological control. These findings extend the limited literature regarding the 2 × 2 framework of achievement goals and enable us to evidence the mediating and suppressing effects of achievement goals. This study highlights the importance of parenting in adolescents’ school adjustment through the cultivation of different achievement goals.